2018
DOI: 10.1007/s00380-018-1243-0
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial function in obese and non-obese patients undergoing percutaneous pulmonary vein isolation

Abstract: Obesity constitutes a risk factor for atrial fibrillation (AF) and modifies the efficacy of invasive AF treatment. Left atrial (LA) global longitudinal strain (GLS), which is measured using speckle-tracking echocardiography (STE), is one of the new methods that are helpful in evaluating the function of LA. The aim of the study was to evaluate LA function in obese and non-obese patients that were undergoing percutaneous pulmonary vein isolation (PVI) before and 6 months after the procedure. 89 patients (F/M: 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…This finding is in line with the results of Gulel et al [32] who found no significant differences in LA mechanical function assessed by LAS. More recently, Cichón et al [33] , reported no significant differences in LASr in the 4-chamber view with a significant yet clinically minimal difference in the 2-chamber view. In contrast, Chirinos et al [34] showed a reduced LASr and LASc with a higher LASb function among overweight and obese middle-age adults.…”
Section: Discussionmentioning
confidence: 94%
“…This finding is in line with the results of Gulel et al [32] who found no significant differences in LA mechanical function assessed by LAS. More recently, Cichón et al [33] , reported no significant differences in LASr in the 4-chamber view with a significant yet clinically minimal difference in the 2-chamber view. In contrast, Chirinos et al [34] showed a reduced LASr and LASc with a higher LASb function among overweight and obese middle-age adults.…”
Section: Discussionmentioning
confidence: 94%
“…It seems that there is a strong association between reduction in LV filling pressure and improvement in LA function as indicated by the enhancement in LA strain. 20 Decreased LA strain has been found to be related to the LV diastolic dysfunction. 21 Moreover, it has been reported that LA strain has depressed in comorbid conditions associated with diastolic dysfunction, such as diabetes 22 and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…FABP3 may be used as an indicator of the early atrial functional injury caused by higher BMI. Clinically, increased BMI has been associated with LA enlargement and impaired LA global longitudinal strain (5,6). We have previously shown that in a rat heart failure model with metabolic syndrome, the LA remodeling and loss of atrial function in vivo are direct consequences of the adipose phenotype (21).…”
Section: Discussionmentioning
confidence: 99%
“…Since many recent studies have shown a significant correlation between BMI and atrial remodeling in recent years (4)(5)(6), underlying the overweight-and obesity-related molecular biology mechanisms are yet poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation